New Elaborated Technique for Isolation and Purification of Limonene from Orange Oil: Isolation of limonene from orange oil - Amanzadeh, Yaghoub; Ashrafi, Mani; Mohammadi, Fatemeh (Iranian Journal of Pharmaceutical Sciences, 2006)
Essential oil of the orange peel which was extracted by hydrodistillation method showed 50 different mono- and sesquiterpenes on GC-MS analysis, in which limonene had the highest percentage (92.4%). Due to various important uses of the compound, a method was developed for isolation and purification of limonene. In this method, for extra purification, a fractional distillation on Vigreux column under 100 mm Hg vacuum was used which resulted in 96.7% purity for limonene. Subsequent chromatography by two different packages of silica gel and active charcoal columns resulted in 99.4% and 99.9 % purity of limonene, respectively.